Effect of interfacial treatment on the thermal properties of thermal conductive plastics (eXPRESS Polymer Letters, 2007)
In this paper, ZnO, which is processed by different surface treatment approaches, is blended together with polypropylene to produce thermal conductive polymer composites. The composites are analyzed by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) to investigate the surface modification of filler, their distribution in the matrix and the condition of two-phase interface. Optimized content of filler surface modifier is investigated as well. The results showed that using low-molecular coupling agent produces positive effect to improve the interface adhesion between filler and matrix, and the thermal conductivity of the composite as well. Macro-molecular coupling agent can strongly improve two-phase interface, but it is not beneficial at obtaining a high thermal conductivity. The blend of ZnO without modification and polypropylene has many defects in the two-phase interface, and the thermal conductivity of the composite is between those of composites produced by previous two approaches. The surface treatment of the filler also allowed producing the composites with lower coefficient of thermal expansion (CTE). As for the content of low-molecular coupling agent, it obtains the best effect at 1.5 wt%.